2007
DOI: 10.1002/jbm.a.31215
|View full text |Cite
|
Sign up to set email alerts
|

Biological stability of polyurethane modified with covalent attachment of di‐tert‐butyl‐phenol

Abstract: Polyurethane cardiovascular implants are subject to oxidation initiated surface degradation, which is mediated by monocyte-derived macrophages (MDM); this often leads to surface cracking and device failure. The present studies examined the hypothesis that covalently attaching antioxidant, di-tert-butylphenol (DBP), to the urethane nitrogens of a polyether polyurethane (PU) via bromo-alkylation reactions could prevent this problem. PU was configured with two dosages of DBP, 0.14 mM DBP/g PU of DBP (PU-DBP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…FTIR analysis has shown that the oxidation of polyurethane elastomers corresponds with an increase in peak intensity at the 1174 cm −1 , assigned to the ʋ(C-O-C) of branched ether, which has been identified as a marker of oxidative degradation [14, 18, 19, 26]. The extent of ether cross-linking is quantitatively determined by normalizing the 1174 cm −1 spectral peak intensity with the peak intensity of the 1590 cm −1 spectral peak, which corresponds to a non-oxidized aromatic ring [14, 18, 19, 26]. Shown in Figure 6B (Spectra shown in Supplemental Data Figure 5), the immobilization of either hCD47 or bCD47 significantly reduced the cross-linking of the polyurethane’s ether groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…FTIR analysis has shown that the oxidation of polyurethane elastomers corresponds with an increase in peak intensity at the 1174 cm −1 , assigned to the ʋ(C-O-C) of branched ether, which has been identified as a marker of oxidative degradation [14, 18, 19, 26]. The extent of ether cross-linking is quantitatively determined by normalizing the 1174 cm −1 spectral peak intensity with the peak intensity of the 1590 cm −1 spectral peak, which corresponds to a non-oxidized aromatic ring [14, 18, 19, 26]. Shown in Figure 6B (Spectra shown in Supplemental Data Figure 5), the immobilization of either hCD47 or bCD47 significantly reduced the cross-linking of the polyurethane’s ether groups.…”
Section: Resultsmentioning
confidence: 99%
“…Male Sprague Dawley rats, weighing between 300 and 350 grams were used for subdermal implant studies as previously described [18]. Rats were anesthetized with isoflurane and administered Flunixamine post surgery for analgesia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[83][84][85][86] With respect to pacemaker leads, which commonly use polyurethane insulation, the duration from implantation to device failure has been shown to be as short as $2.5 years. 87 Laboratories, including our own, have tried to address the issue of oxidative degradation of polyurethane by coblending 84 or covalently linking 86,88 phenol-based antioxidants to polyurethane preparations. The limitations of this approach lie primarily in the fact that the antioxidants are expended once they react with hydroxy radicals.…”
Section: Cd47-modified Polymersmentioning
confidence: 99%